2021
DOI: 10.1039/d0ra07727e
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of rhodamine B with cavitation technology: comparison of hydrodynamic cavitation with ultrasonic cavitation

Abstract: This paper presents the use of hydrodynamic cavitation and ultrasonic cavitation technologies for treating rhodamine B (RhB) in simulated wastewater.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(4 citation statements)
references
References 34 publications
0
1
0
Order By: Relevance
“…In this experiment, there exist many tiny bubbles (cavitation nuclei) in the solution due to the stirring during the solution preparation. These microbubbles in sessile droplet were activated by ultrasound and experienced a dynamic process including oscillation, growth, contraction and explosion, that is, ultrasonic cavitation effect [39] , [40] , [41] .
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…In this experiment, there exist many tiny bubbles (cavitation nuclei) in the solution due to the stirring during the solution preparation. These microbubbles in sessile droplet were activated by ultrasound and experienced a dynamic process including oscillation, growth, contraction and explosion, that is, ultrasonic cavitation effect [39] , [40] , [41] .
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Although, in principle, it is possible to use pseudo- n th order kinetics, most of the reports describing experimental data on pollutant degradation using hydrodynamic cavitation have used pseudo-first order kinetics. Several studies are published using this approach. This approach of using a pseudo-first order rate constant for describing the hydrodynamic cavitation process has been shown to not be appropriate by Ranade et al They had clearly shown that this approach would predict two different values of the effective rate constant for the same hydrodynamic cavitation reactors under the same operating conditions for different volume of the holding tank ( k app = 1.06 × 10 –3 min –1 for 0.005 m 3 volume in the holding tank and k app = 2.41 × 10 –4 min –1 for 0.024 m 3 volume in the holding tank). It is unphysical to expect dependence of the effective rate constant on the volume of the holding tank!…”
Section: Current Status Of Modeling Of Hydrodynamic Cavitation Reacto...mentioning
confidence: 99%
“…Also, in various branches of industry, the effect of a magnetic field is widely used to change the properties of water [16][17][18]. The study of cavitation in low-frequency sound fields revealed an analogy in terms of physicochemical effects between low-frequency and ultrasonic cavitation [19,20].…”
Section: Introductionmentioning
confidence: 99%